Iron supplementation for lambs experimentally infected by Haemonchus contortus: Response to anemia and iron store in the bone marrow - Casanova V.P. (2018)
© 2018 Colegio Brasileiro de Patologia Animal. All rights reserved.To evaluate the effect of supplementation of iron dextran on blood variables and iron metabolism in lambs experimentally infected by Haemonchus contortus, four experimental groups were used: uninfected and non-supplemented animals (GI); infected animals supplemented with iron (GII); uninfected animals supplemented with iron (GIII); and infected non-supplemented animals (GIV). Groups II and IV received 10,000 larvae (L3) of Haemonchus contortus, and groups II and III received three doses of iron dextran (20mg/kg) intramuscularly with seven days of interval. Blood and faeces samples were collected on days 10 (D10), 17 (D17), 24 (D24), and 31 (D31), in order to determine red blood cell counts, iron metabolism, and EPG. Infected animals developed anemia from D24 and anemia was more severe on D31. Animals from GII had higher hematocrit and hemoglobin concentration compared to animals of GIV on D31. Iron stores in the bone marrow were higher in GII and GIII compared to GI and GIV. The GIV showed lower seric levels of iron on D24 compared to the other groups. The iron supplementation reduces the severity of the anemia caused by infection with Haemonchus contortus in lambs, improving erythropoietic response after blood loss.